SOME LEGAL AND ACCOUNTING QUESTIONS PRESENTED BY THE MICHIGAN GENERAL CORPORATION ACT. - Lewis, Fletcher (The Accounting Review, 1933)
The article presents information related to some legal and accounting questions presented by the Michigan General Corp. Act. In accepting the invitation from the Michigan Society of Certified Public Accountants to discuss the legal and accounting questions involved in the capital stock provisions of the Michigan General Corp. Act adopted in 1931, it was understood that the discussion of the author would be primarily from the viewpoint of the corporation lawyer. Although the author is not an accountant and does not profess to have any technical knowledge of the theoretical accounting problems, nevertheless, in the actual practice of corporation law it becomes essential to gain some understanding of certain accounting principles involved in the preparation of a corporate balance sheet and presented in every corporate security issue. These accounting principles are interrelated with important legal principles and are of general application quite independent of the provisions of any particular corporate statute.